Role Of Complex Nutrients On Production Of L-Glutamic Acid By Amutant Micrococcus Glutamicus Ab100. - S. GANGULY,; A. K. BANIK, (International Journal of Pharma and Bio Sciences, 2011)
The effect of some complex nutrients like wheat bran extract, rice bran extract, paddy soak liquor, tryptone, soybean extract, corn steep liquor, peptone, yeast extract, malt extract and beef extract on l-glutamic acid fermentation by a mutant Micrococcus glutamicus AB100 were investigated. Different concentrations (02-0.5%) of each of the complex nutrients were added to the fermentation broth. Production of l-glutamic acid was decreased with wheat bran extract, rice bran extract, paddy soak liquor and tryptone but increased significantly with soybean extract, 0.3%; corn steep liquor, 0.25%; peptone, 0.3%; yeast extract, 0.4% malt extract, 0.3% and beef extract, 0.4%.